Pengaruh Pengalaman Audit, Skeptisme Profesional Dan Time Pressure Terhadap Kemampuan Auditor Mendeteksi Fraud - Safira Indriyani; Luqman Hakim (Universitas Muhammadiyah Jakarta, 2021)
The research purposes to obtain and understand the empirical evidence about audit experience, auditor’s professional scepticism and time pressure toward auditor’s ability to detect fraud. The research method used was quantitative by using primary data questionnaires to the Public Accounting Firm in Center Jakarta. Sample taking method on this research is using simple random sampling. The result showed that audit experience and auditor’s professional scepticism have positive and significant effect on auditor’s ability to detect fraud, time pressure has negative and significant effect on auditor’s ability to detect fraud.